Adipsic Diabetes Insipidus—The Challenging Combination of Polyuria and Adipsia: A Case Report and Review of Literature - Dalan, Rinkoo; Chin, Hanxin; Hoe, Jeremy; Chen, Abel; Tan, Huiling; Boehm, Bernhard Otto; Chua, Karen SuiGeok (Frontiers in Endocrinology, 2019)
Adipsic Diabetes Insipidus is a rare hypothalamic disorder characterised by a loss of thirst in response to hypernatraemia accompanied by diabetes insipidus. These occur secondary to a congregation of defects in the homeostatic mechanisms of water balance. A 27-year old Chinese female presented with Adipsic Diabetes Insipidus after cerebral arteriovenous malformation (AVM) surgery. Initial diagnosis and management was extremely challenging. Long term management required a careful interplay between low dose vasopressin analogue treatment and fluids. Detailed charts of medication and sodium balance are described in the case presentation. We performed a literature search of similarly reported cases and describe the possible pathogenesis, aetiology, clinical presentation, acute and chronic management and prognosis.